The Utility of FDG-PET/CT in Clinically Suspected Paraneoplastic Neurological Syndrome: A Literature Review and Retrospective Case Series - Maskery, Mark P.; Hill, Jonathan; Cain, John R.; Emsley, Hedley C. A. (Frontiers in Neurology, 2017)
Paraneoplastic neurological syndrome (PNS) describes a spectrum of rare, heterogeneous neurological conditions associated with an underlying malignancy. Diagnosis of PNS is inherently difficult, with frequent misdiagnosis and delay. The literature suggests an underlying immune mediated pathophysiology and patients are usually tested for the presence of onconeural antibodies. With direct tumor therapy being the most effective method of stabilizing patients there is a strong emphasis on detecting underlying tumors. The sensitivity of conventional CT imaging is often inadequate in such patients. Whilst FDG-PET imaging has already been shown to be effective at detecting these tumors, FDG-PET/CT, combining both structural and functional imaging in a single study, is a more recent technique. To study the utility of FDG-PET/CT we conducted a systematic literature review and a retrospective study. We identified 41 patients who underwent imaging for clinically suspected PNS at the regional PET-CT and neurosciences center based at the Royal Preston Hospital between 2007 and 2014 and compared the results to conventional investigations. Five patients had FDG-PET/CT tracer avidity suspicious of malignant disease, and 4 of these were subsequently diagnosed with cancer. Sensitivity and specificity were calculated to be 100% and 97.3% respectively with positive predictive value (PPV) 80% and negative predictive value (NPV) 100%. This compares to a sensitivity and specificity of 50% and 100% respectively for CT and 50% and 89% respectively for onconeural antibodies. These findings are in line with previous studies and support the diagnostic accuracy of FDG-PET/CT for the detection of underlying malignancy.